Pengaruh Pemanasan Kelapa Parut Dan Teknik Pengunduhan Terhadap Rendemen Dan Mutu Virgin Coconut Oil (VCO) - Sutardi .; Umar Santoso; Anggia . (PERTETA, 2008)
Virgin Coconut Oil (VCO) was produced from green variety ofnon-hybride coconut type. Grated coconut was heated at 500, 70°, and 90°C for 20, 30 and 40 minutes, respectively. Harvesting technique of VCO were done by conventional, utilization of stainless steel screen, and filter paper laminated stainless steel screen methods, respectively. Produced VCO was subsequently analyzed their productivity and quality parameters consisting of moisture content, acid number, free fatty acid (FFA), peroxide number, iodine number, saponification number, clearness and fatty acid profile of VCO. Statistical analysis was also conducted by using Analysis of Variance and Duncan Multiple Range Test with 5% significancy.The results showed that heating ofgrated coconut at 900C for 40 minutes produced 29.65 ±0.38% VCO, and it was the highest productivity.-Heating temperature ofgrated coconut and with any harvesting technique didn't statistitically have significant effect on productivity and quality of VCO. While, combination of heating temperature at 90°C and it was followed by harvesting technique using stainless steel screen produced the highest VCO i.e. 31.54 ± 0.58%. The best quality of VCO was characterized by 0.09 ± 0.01% moisture content, 0.20 ± 0.02 mg KOH/g oil of acid number, 0.12 ± 0.01% free fatty acid (FFA), 0.37 ± 0.01 meq/kg oil ofperoxide number, 5. 11 ± 0.01 g iod/100 g oil ofiodine number, 244. 12 ± 0.01 mg KOH/g oil saponification number and the VCO was clear and transparant. Fatty acid profile of selected VCO was dominated by medium chain fatty acid (C12:0) particularly lauric acid i.e. 50.26% and followed by 8.65% caprylic and 5,73% capric acids, respectively.